1979
DOI: 10.1111/j.1096-3642.1979.tb01903.x
|View full text |Cite
|
Sign up to set email alerts
|

A new form of insect cuticle

Abstract: A hitherto unnoticed, harder form of cuticle, whirh occurs on the mandibles ofthe Austi-alian plague locust, Chortozceles tprrninzfera, is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1984
1984
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Neville et al (30) reported that a common arrangement of chitin crystallites embedded in the matrix of proteins in the procuticle of arthropods including insects is a hexagonal or pseudo hexagonal lattice with a size range of ϳ4.5-9.0 nm for each side. Nanofibers with diameters ranging from 20 to 100 nm in cicada cuticles (31), 25 nm in the claval furrow of L. migratoria (32), and 160 -300 nm in the jaws of the Australian plague locust (33) have been reported. Nanofibers with a diameter of 50 -250 nm and a length of 300 nm have been proposed as the building blocks of horizontally stacked laminae (34).…”
Section: Group I Chitin Deacetylases and Insect Cuticle Structurementioning
confidence: 99%
“…Neville et al (30) reported that a common arrangement of chitin crystallites embedded in the matrix of proteins in the procuticle of arthropods including insects is a hexagonal or pseudo hexagonal lattice with a size range of ϳ4.5-9.0 nm for each side. Nanofibers with diameters ranging from 20 to 100 nm in cicada cuticles (31), 25 nm in the claval furrow of L. migratoria (32), and 160 -300 nm in the jaws of the Australian plague locust (33) have been reported. Nanofibers with a diameter of 50 -250 nm and a length of 300 nm have been proposed as the building blocks of horizontally stacked laminae (34).…”
Section: Group I Chitin Deacetylases and Insect Cuticle Structurementioning
confidence: 99%
“…It is well adapted to its function and varies from a thin, delicate, transparent membrane, such as that over a receptor, to the thick, tough and rigid armour present in many beetles and crustaceans. Mouthparts are sclerotized cuticle and in three locust species (Gardiner and Khan 1979) a harder form of mandibular cuticle covers the normal cuticle (cf. 30.2.8).…”
Section: Stabilization Of Cuticlesmentioning
confidence: 99%